Towards a better understanding of carotenoid metabolism in animals - Von Lintig, J.; Hessel, S.; Isken, A.; Kiefer, C.; Lampert, J.M.; Voolstra, O.; Vogt, K.
Vitamin A derivatives (retinoids)are essential components in vision; they contribute to pattern formation during development and exert multiple effects on cell differentiation with important clinical implications. All naturally occurring vitamin A derives by enzymatic oxidative cleavage from carotenoids with provitamin A activity. To become biologically active, these plant-derived compounds must first be absorbed, then delivered to the site of action in the body, and metabolically converted to the real vitamin. Recently, molecular players of this pathway were identified by the analysis of blind Drosophila mutants. Similar genome sequences were found in ertebrates. Subsequently, these homologous genes were cloned and their gene products were functionally characterized. This review will summarize the advanced state of knowledge about the vitamin A biosynthetic pathway and will discuss biochemical, physiological, developmental and medical aspects of carotenoids and their numerous derivatives.
Keywords: VITAMIN A; CAROTENOID METABOLISM IN ANIMAL; BCO; BCO2; RPE65; RETINOIC ACID SIGNALING